(untitled) (International Journal of Engineering and Computer Science, 2017)
Using the cloud storage, users store their data on the cloud without the burden of data storage and maintenance and services and high-quality applications from a shared pool of configurable computing resources. Cryptography is probably the most important aspect of communications security and is becoming increasingly important as a basic building block for computer security. As data sharing is an important functionality in cloud storage, In this paper we show that how to securely, efficiently and flexibly share data with others in cloud storage, Cloud-validation based Flexible Distributed, Migration, ciphertext with aggregate key encryption for data stored in cloud. This scheme provides secure data storage and retrieval. Along with the security the access policy is also hidden for hiding the user’s identity. This scheme is so powerful since we use aggregate encryption and string matching algorithms in a single scheme. The scheme detects any change made to the original file and if found clear the error’s. The algorithm used here are very simple so that large number of data can be stored in cloud without any problems. The security, authentication, confidentiality are comparable to the centralized approaches. A set of constant-size cipher texts such that efficient delegation of decryption rights for any set of cipher texts is possible the best.